EFEKTIFITAS PENGGUNAAN MEDIA POP UP BOOK TERHADAP KEMAMPUAN MENGENAL BILANGAN 1-10 PADA ANAK TUNAGRAHITA RINGAN KELAS II SDLB YPBB KARIMUN - Muhiri; Siti Rumaiyah; Eka Lenggang Dianasari; Karunia Yulinda Khairiyah (JURNAL JUDIKHU, 2022)
This study aims to determine the effectiveness of using pop up book media on the ability to recognize numbers 1-10 in mild mentally retarded children at SDLB YPBB Karimun. This type of research is a quantitative research with a single subject approach (single subject research) which focuses on individual data as research samples. The results of the study concluded that the use of pop up book media can improve the ability to recognize numbers 1-10 students with mild mental retardation class II SDLB YPBB Karimun. In the baseline condition (AI) the ability of mentally retarded students is still low with a mean level of 53.25%, then after being given treatment or in the Intervention condition (B) there is an increase in the ability to recognize numbers 1-10 with a mean level of 69% and can be maintained at the Baseline condition ( A2) with the mean level increasing to 85%. Thus the pop up book media can improve the ability to recognize the number of children with mild mental retardation II SDLB YPBB Karimun.